Pengaruh Mutasi terhadap Kinerja Karyawan dengan Kepuasan Kerja sebagai Variabel Mediasi (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2024)
Through observations made at BPR. Sedana Yasa Belayu, Tabanan Regency, problems were found related to company performance, namely the company's work plan not being achieved, employee performance not being optimal will affect the stability of the company, where employees with poor performance, lack of work enthusiasm will make the company's targets not achieved so that the company will it is difficult to compete with other companies and in the end it can also go bankrupt. This research was conducted at BPR Sedana Yasa Belayu, Tabanan Regency. The number of respondents was 57 employees using the sample determination method, namely census sampling. Data collection was carried out through observation, interviews, literature studies and questionnaires. The data analysis techniques used are validity test, reliability test, path analysis and Sobell test. Based on the results of the analysis, it was found that the mutation variable had a positive and significant effect on employee satisfaction at BPR Sedana Yasa in Tabanan Regency. The satisfaction variable has a positive and significant effect on employee performance at BPR Sedana Yasa in Tabanan Regency. Likewise, the mutation variable has a positive and significant effect on the performance of BPR Sedana Yasa employees in Tabanan Regency. Satisfaction can mediate the relationship between transfers and employee performance.